Pengetahuan dan Perilaku Masyarakat Dalam Pelaksanaan Protokol Kesehatan di Masa Pandemi Covid-19 - Clara Felicia Regina Fortunata; Retno Puspitadewi, Teresia; Wahyurianto, Yasin (JURNAL KEPERAWATAN, 2023)
The daily increase of cases, with the highest confirmed surge in Covid-19 in the Latsari village, indicates that community compliance with health protocols is still not optimal. The COVID-19 virus continues to spread as a result of non-compliance with health protocols, and it has numerous harmful consequences in various sectors, including health, economic, education, and political sectors. This study aims to describe the knowledge and behavior of the community in implementing health protocols during the COVID-19 pandemic in the RT 03 / RW 02 area, Latsari Village, Tuban District, Tuban Regency. The research design utilized a descriptive method with cross sectional approach. A total of 67 family heads were included in this study, with a sample of 57 families. The sampling technique used in this study was a simple random sampling. Research variables used community knowledge and behavior in implementing health protocols during the COVID-19 pandemic. Meanwhile, the data collecting methods were in the form of a questionnaire. Once the data was collected, it was then processed and tabulated descriptively. According to the results of this study, almost half of the community had a less knowledge about how to implement health protocols during the COVID-19 pandemic, and almost all people had a poor behavior towards the implementation of COVID-19 health protocols. Due to the lack of knowledge and behavior of the community, the number of confirmed cases of COVID-19 increased in RT 03 / RW 02 Latsari Village. Several steps that can be taken as an effort to prevent the spread of COVID-19, are that the community is encouraged to implement the 5M movement (wearing masks, washing hands, maintaining distance, staying away from crowds, limiting mobilization and interaction), and providing a place for washing hands in every house with water flowing and antiseptic soap.